Jornada de protesto contra o apartheid para a liberação de Nelson Mandela - Marcelo, D (JAAC (Juventude Africana Amilcar Cabral), 1986)
Collage of Black hands breaking apart the word 'Apartheid' Poster advertising day of solidarity with Nelson Mandela, and of protest against the apartheid PO-1752